Lower Urinary Tract Obstruction (LUTO) pada fetus: laporan kasus - Rey Jauwerissa; I Nyoman Hariyasa Sanjaya; Endang Sri Widiyanti; Ryan Saktika Mulyana; Evert Solomon Pangkahila (Intisari Sains Medis, 2020)
Background: Lower fetal urinary tract obstruction (LUTO) is an abnormality observed during an ultrasound test in the antenatal period in the form of an enlarged fetal bladder. Oligohydramnios, renal cortex dilation, and pulmonary hypoplasia may be caused by obstruction of the lower urinary tract. In the management of LUTO, early diagnosis and assessment as early as possible are very important. The insertion of a shunt from the fetal bladder to the amniotic cavity is one of the therapies for fetal LUTO (vesicoamniotic shunt). This case study aims to determine the management of LUTO in fetuses at Sanglah Hospital, Bali, Indonesia. Case Presentation: A 39-year-old female G3P2002 was referred to the obstetrics and gynecology clinic of Sanglah Hospital with suspected fetal LUTO for 18-19 weeks. There were no complaints or risk factors for LUTO in the past. Physical examination and obstetric examinations were within normal limits. On ultrasound examination, there was a hypohyperechoic image measuring 4.3 x 5.3 cm with the impression of the enlarged bladder, key-hole appearance, oligohydramnios, and bilateral hydronephrosis. Double pigtail installation on the fetus, amnioinfusion, and amniosynthesis was performed for karyotyping. Ten weeks after double pigtail placement, the patient developed premature labor and subsequently gave birth to a baby boy, LBW 1,800 gram, with severe asphyxia, Potter facies, abdominal distension, and leg deformities. Unfortunately, the baby eventually died 1 hour postpartum.Conclusion: Overall, infants have a poor prognosis for fetal LUTO cases. In assessing the effectiveness of treatment, early diagnosis, assessment, and early intervention are very critical. Latar Belakang: Lower Urinary Tract Obstruction (LUTO) pada fetus merupakan suatu kelainan pada periode antenatal berupa pembesaran kandung kemih fetus yang ditemukan pada pemeriksaan USG. Sumbatan saluran kemih bagian bawah tersebut dapat menyebabkan oligohidramnios, pelebaran korteks ginjal, hingga hipoplasia paru. Diagnosis awal dan evaluasi sedini mungkin sangat penting dalam penanganan LUTO. Salah satu penanganan fetal LUTO adalah dengan pemasangan shunt dari vesika urinaria fetus ke rongga amnion (vesicoamniotic shunt). Laporan kasus ini bertujuan untuk mengevaluasi penanganan LUTO terhadap fetus di RSUP Sanglah, Bali, IndonesiaPresentasi Kasus: Seorang perempuan 39 tahun G3P2002 18-19 minggu dirujuk ke poliklinik kebidanan dan kandungan RS Sanglah dengan kecurigaan fetal LUTO. Pada anamnesis tidak didapatkan keluhan maupun faktor risiko LUTO. Pemeriksaan fisis dan pemeriksaan obstetri dalam batas normal. Pada pemeriksaan USG didapatkan gambaran hipohiperekoik berukuran 4,3 x 5,3 cm dengan kesan vesika urinaria membesar, key-hole appearance, oligohidramnios dan hidronefrosis bilateral. Dilakukan tindakan pemasangan double pigtail pada fetus, amnioinfusion serta amniosintesis untuk pemeriksaan karyotyping. Sepuluh minggu setelah pemasangan double pigtail, pasien mengalami partus prematurus imminens dan selanjutnya melahirkan bayi lelaki, BBL 1.800 gram, dengan asfiksia berat, Potter facies, distensi abdomen dan deformitas tungkai. Sayangnya, bayi akhirnya meninggal 1 jam pasca-persalinan.Kesimpulan: Secara keseluruhan kasus fetal LUTO memiliki prognosis yang kurang baik bagi bayi. Diagnosis awal, evaluasi dan intervensi sedini mungkin sangat penting dalam menentukan keberhasilan terapi.